2017
DOI: 10.1002/jbt.22004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antithrombotic and cytotoxicity effects of ferulic acid

Abstract: We discovered recently in vitro and in vivo antithrombotic and cytotoxicity effects of ferulic acid.The cytotoxicity assays showed that ferulic acid (∼300 g/mL) did not cause any significant toxicity on three cell lines, platelets, leukocytes, and erythrocytes. In vitro assays showed inhibitory effects of ferulic acid on thrombin (THR)-or collagen/epinephrine-stimulated platelet activation by inhibiting platelet aggregation, and decreasing clot retraction activity. The in vitro effect of ferulic acid on THR-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…Ferulic acid at the concentration of 300 µL/mL showed no significant cytotoxicity. Additionally, the inhibition of platelet aggregation and an anticoagulant effect was observed [113]. Ferulic acid is a free radical scavenger and inhibits the activity of the enzymes responsible for free radical generation catalysis.…”
Section: Collagen-ferulic Acidmentioning
confidence: 99%
“…Ferulic acid at the concentration of 300 µL/mL showed no significant cytotoxicity. Additionally, the inhibition of platelet aggregation and an anticoagulant effect was observed [113]. Ferulic acid is a free radical scavenger and inhibits the activity of the enzymes responsible for free radical generation catalysis.…”
Section: Collagen-ferulic Acidmentioning
confidence: 99%
“…It exerts antitumor activity and inhibits metastasis of breast cancer cells by regulating epithelial to mesenchymal transition, and it exerts neuroprotective effects against cerebral ischemia/reperfusion‐induced injury via antioxidant and antiapoptotic mechanisms . Recently, FA was also shown to inhibit the clot retraction responsible for platelet development . However, the difference between the influence on the cell and the living body due to the introduction of a bromide onto FA is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…15 Recently, FA was also shown to inhibit the clot retraction responsible for platelet development. 16 However, the difference between the influence on the cell and the living body due to the introduction of a bromide onto FA is unclear. Therefore, we investigated the cytotoxicity of FA and 6-BFA by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay at concentrations of 1, 10, 50, 100, and 1000 μM against PC12 cells.…”
Section: In Vitro Assay Of Fa and 6-bfamentioning
confidence: 99%
“…Choi et al . ( 38 ) found that a ferulate treatment up to 1.54 mM did not show any toxicity on NIH-3T3, HepG2, or 3T3-L1 cells. Additionally, 5.1 mM ferulate treatment for 7 days did not exhibit toxicity on human bone marrow stromal cells ( 39 ).…”
Section: Discussionmentioning
confidence: 97%